GmCLC1 Confers Enhanced Salt Tolerance through Regulating Chloride Accumulation in Soybean - Wei, Peipei; Wang, Longchao; Liu, Ailin; Yu, Bingjun; Lam, Hon-Ming (Frontiers in Plant Science, 2016)
The family of chloride channel proteins that mediate Cl- transportation play vital roles in plant nutrient supply, cellular action potential and turgor pressure adjustment, stomatal movement, hormone signal recognition and transduction, Cl- homeostasis, and abiotic and biotic stress tolerance. The anionic toxicity, mainly caused by chloride ions (Cl-), on plants under salt stress remains poorly understood. In this work, we investigated the function of soybean Cl-/H+ antiporter GmCLC1 under salt stress in transgenic Arabidopsis thaliana, soybean, and yeast. We found that GmCLC1 enhanced salt tolerance in transgenic A. thaliana by reducing the Cl- accumulation in shoots and hence released the negative impact of salt stress on plant growth. Overexpression of GmCLC1 in the hairy roots of soybean sequestered more Cl- in their roots and transferred less Cl- to their shoots, leading to lower relative electrolyte leakage values in the roots and leaves. When either the soybean GmCLC1 or the yeast chloride transporter gene, GEF1, was transformed into the yeast gef1 mutant, and then treated with different chloride salts (MnCl2, KCl, NaCl), enhanced survival rate was observed. The result indicates that GmCLC1 and GEF1 exerted similar effects on alleviating the stress of diverse chloride salts on the yeast gef1 mutant. Together, this work suggests a protective function of GmCLC1 under Cl- stress.